Optimalisasi Fungsi ASEAN Intergovernmental Commission on Human Rights (AICHR) dan Tantangan Perlindungan Hak Asasi Manusia di Asia Tenggara - Sigit Riyanto (Fakultas Hukum Universitas Islam Indonesia, 2024)
Pursuant to the 2008 Charter, ASEAN has worked with a new legal framework and has thus established various organs to accelerate the process of community building. In accordance with the said Charter, ASEAN established a Human Rights Body namely the ASEAN Intergovernmental Commission on Human Rights (AICHR). AICHR serves as a human rights institution which is designated as an integral part of ASEAN that is responsible for promoting and protecting human rights according to the objectives and principles in the ASEAN Charter. In the light of their human rights protection efforts, AICHR has exhibited promising achievements. On the other hand, however, AICHR is considered ineffective as it has not achieved significant results in terms of protecting and upholding human rights in Southeast Asia. This research is intended to conduct a critical study of the role and function of AICHR in dealing with contemporary human rights problems and challenges. By observing the contemporary human rights problems and challenges in Southeast Asia, it is strongly recommended that ASEAN immediately adjust and expand the mandate of the AICHR. Adjusting and expanding AICHR's mandate can strengthen AICHR's structure and authority as an institution that safeguards human rights in Southeast Asia. Strengthening the AICHR will contribute to the protection and upholding of human rights and increase ASEAN's credibility as a Regional Organization.Keywords: AICHR, ASEAN, Enforcement, Human Rights, Protection. AbstrakBerdasarkan Piagam tahun 2008, ASEAN bekerja dengan kerangka hukum baru dan membentuk berbagai organ yang diperlukan untuk mempercepat proses membangun komunitas. Sesuai dengan Piagam, ASEAN membentuk Badan HAM yang dinamai ASEAN Intergovernmental Commission on Human Rights (AICHR). AICHR merupakan lembaga HAM yang dirancang sebagai bagian integral ASEAN yang bertanggungjawab dalam upaya promosi dan perlindungan HAM. Sesuai dengan tujuan dan prinsip-prinsip di dalam Piagam ASEAN. Dalam upaya promosi HAM, AICHR telah membuktikan capaian yang menjanjikan, namun, dalam hal perlindungan dan penegakan HAM, AICHR dianggap belum efektif. AICHR belum mencapai hasil yang signifikan dalam hal perlindungan dan penegakan HAM di Asia Tenggara. Penelitian ini dimaksudkan untuk melakukan kajian kritis tentang peran dan fungsi AICHR dalam menghadapi permasalahan dan tantangan HAM kontemporer. Mencermati permasalahan dan tantangan HAM kontemporer di Asia Tenggara, sangat disarankan ASEAN segera melakukan penyesuaian dan perluasan mandat AICHR. Penyesuaian dan perluasan mandat AICHR dapat memperkuat struktur dan otoritas AICHR sebagai institusi pengawal HAM di Asia Tenggara. Penguatan AICHR akan berkontribusi pada perlindungan dan penegakan HAM serta meningkatkan kredibilitas ASEAN sebagai Organisasi Regional.Kata Kunci: AICHR, ASEAN, Hak Asasi Manusia, Penegakan, Perlindungan.